Data Report on School Dropout in a Brazilian State: Social Technologies for Preventing the Phenomenon - Freires, Leogildo Alves; Araújo, Heitor Marinho da Silva; Torres, Luan Filipy Freire; Cordeiro, Thiago Damasceno; Macedo, Gabriel Fortes Cavalcanti de (Conference on Digital Government Research, 2025)
School dropout is a multifaceted and persistent challenge with serious implications for public health, economic development, and social equity. In Brazil, where educational disparities remain deeply rooted in structural and contextual inequalities, addressing dropout requires more than tracking attendance, academic performance, or behavior. This study presents the development and implementation of a Relational Model (RM) aimed at identifying and mitigating school dropout risks through a comprehensive, data-informed approach. Central to this model is the Alternative Instrument for Assessing School Dropout Risk Factors (IAFREE-A), which evaluates 13 interrelated risk factors across five key dimensions: Student-School, Student-School Professionals, Student-Family, Student-Community, and Student-Student. These dimensions allow for a nuanced understanding of how relational dynamics and contextual conditions shape students’ engagement with schooling. A pilot study was carried out in the state of Mato Grosso, involving 624 students across 10 public schools. Data collection was conducted through physical questionnaires, digitized using Optical Character Recognition (OCR) technology, and processed via an integrated digital platform. This platform generates individual and institutional dropout risk profiles by mapping protective and risk factors, providing actionable insights for educators, school administrators, and policymakers. Results highlighted critical concerns such as inadequate school infrastructure, perceptions of insecurity, and weak family-school connections, reinforcing the need for early, context-specific interventions. The findings demonstrate that school dropout is not an isolated event, but the outcome of complex relational, institutional, and structural factors. The RM and IAFREE-A offer an innovative and culturally sensitive framework for prevention, enabling tailored interventions that respond to students’ lived realities. By fostering stronger connections among students, educators, families, and communities, this approach has the potential to reduce dropout rates and promote more equitable and supportive educational environments in Brazil and beyond.